2017
DOI: 10.1111/tmi.12882
|View full text |Cite
|
Sign up to set email alerts
|

Optimal antiretroviral therapy adherence as evaluated by CASE index score tool is associated with virological suppression in HIV‐infected adults in Dakar, Senegal

Abstract: Optimal ART adherence is achievable in a high proportion of HIV-infected adults in this study population. CASE Index Score was independently associated with virological outcomes, supporting usefulness of this low-cost ART adherence monitoring tool in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Other studies reported no association between ART adherence and sex, education, or income ( 38 ). According to Byabene et al ( 39 ), high ART adherence was not associated with time to the clinic (travel burdens) ( p = 0.07) ( 39 ).…”
Section: Discussionmentioning
confidence: 98%
“…Other studies reported no association between ART adherence and sex, education, or income ( 38 ). According to Byabene et al ( 39 ), high ART adherence was not associated with time to the clinic (travel burdens) ( p = 0.07) ( 39 ).…”
Section: Discussionmentioning
confidence: 98%
“…Other studies found no association between adherence to ART and age, sex, education 30–40. Byabene et al (2017) reported that adherence to ART was not associated with time to clinic (travel burdens) (p = 0.07) 41…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the behaviour of people on ART [ 15 , 21 , 25 , 63 , 65 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 ]…”
Section: Resultsmentioning
confidence: 99%